PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) DALAM PEMBERDAYAAN MASYARAKAT DI DESA TERAPUNG (Fakultas Dakwah dan Komunikasi, 2020)
This research about the management of the village-owned enterprise (BUMDes) in community empowerment in floating village Mawasangka District, central Buton Regency. The type of research used qualitative descriptive research. The results showed that the management of BUMDes in community empowerment, in general, has been maximal such as financial services (save loan), Moleng rental business, musical instrument rental business, party equipment rental business (tent and chairs). Supporting factor management of BUMDes in the floating village community Empowerment is the availability of BUMDes facilities, the support from the village government is the provision of the budget for the initial capital BUMDes as well as the relationship between the management of BUMDes with the village community. The management of BUMDes in the empowerment of floating village community is limited capital of BUMDes floating village is still less, lack of human resources (HR), and the number of members of BUMDes is still lacking.